Penggunaan Google Cloud Platform untuk Marketeer dan Analis dalam Pengolahan Data - Dzikriyana Zuhdia Aziz; Feri Sulianta (Syntax Idea, 2022)
There are several agencies or companies still use perform manual data analysis using an inefficient platform. This has several drawbacks such as slow data analysis and reporting, thus it is necessary to have a platform and integration process that is easy to use in the data processing and reporting process, because in the process there are still many platforms that are difficult to use and make the analysis process slow. So in this research, Google Cloud Platforms such as Google Analytic, BigQuery & Data Studio are used as a platform to make it easier for marketers and analysts to process data on the KPIs & Metrics that they have determined.